2014
DOI: 10.2478/adms-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Relationships in Nanotubes Formed by Anodizing of Ti6al4v Alloy

Abstract: The electrochemical formation of oxide nanotubes on the Ti6Al4V alloy has been so far difficult due to easy dissolution of vanadium reach β-phase of the two phase material. Due to the topographical heterogeneity of the anodic layer in nano and microscale at anodizing of the Ti6Al4V alloy we focused to establish the relationships between nanotube diameters on both phases of the alloy and fluorides concentration in electrolyte. We studied the effect of fluoride concentration (0.5-0.7 wt.%) in 99% ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…e data presented above were proportional to the previously reported studies [48,69,80]. e nanotube dimensions, morphology, and EDS analysis of the anodised Ti-6Al-4V titanium alloy specimens showed a similar trend to those reported in previous publications [79,[89][90][91][92]. e EDS analysis revealed that the anodic layer was composed of titanium, aluminium, vanadium, oxygen, and traces of carbon and fluorine.…”
Section: Upscaling and Optimisationsupporting
confidence: 84%
“…e data presented above were proportional to the previously reported studies [48,69,80]. e nanotube dimensions, morphology, and EDS analysis of the anodised Ti-6Al-4V titanium alloy specimens showed a similar trend to those reported in previous publications [79,[89][90][91][92]. e EDS analysis revealed that the anodic layer was composed of titanium, aluminium, vanadium, oxygen, and traces of carbon and fluorine.…”
Section: Upscaling and Optimisationsupporting
confidence: 84%
“…One of the pioneering efforts to utilize electrochemical anodization as an innovative approach for the surface modification of Ti-based alloys was performed by Dunn et al [ 221 , 222 ], where porous surface coatings are formed by anodization and incorporating antibiotics onto the oxide surface. Zwilling et al [ 223 ] also reported that anodization on Ti and Ti–6Al–4V alloys in the F − ion solution is an effective approach to attain tunable tubular oxide layers under different anodization conditions [ 16 , 17 , 65 , 133 , [224] , [225] , [226] , [227] , [228] , [229] , [230] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] , [246] , [247] , [248] , [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] , [258] , [259] , [260] , [261] , [262] ]. Since the Ti–6Al–4V alloy is a dual-phase alloy, the development kinetics of nanotubes are dissimilar for the α and β phases [ 69 ].…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…According to the research of Kaczmarek-Pawelska and Krasicka-Cydzik [7], the oxide layers that can form on titanium metal are TiO2, Al2O3, VO2, V2O3, and V2O5. The Ti6Al4V metal alloys used in this study were given 2 treatments, without anodization and anodization.…”
Section: Nanotube and Non-nanotube Alloy Metal Ti6al4vmentioning
confidence: 99%
“…The aqueous electrolyte selected in this study was NH4F 0.6% (w/v) in a mixture of ethylene glycol and water with a ratio of 9:1. According to the research of Kaczmarek-Pawelska and Krasicka-Cydzik [7], the concentration of 0.6% (w/v) NH4F in ethylene glycol and water mixtures can form nanotubes in Ti6Al4V metal alloys with a diameter of 50±5 nm. Ethylene glycol is chosen because of its properties as one of the high viscosities (viscous) organic electrolytes.…”
Section: Figure 1 Illustration Of the Manufacture Of Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation